K-wave simulation to understand the photoacoustic signal characteristic from various shapes of nanoparticle - Verawaty (2015)
Photoacoustic imaging technique has been widely discussed for their potential application in biomedical field. Current attempts in understanding the photoacoustic signal characteristics generated from various shapes of nanoparticles are done mostly through experimental synthesis which are usually time consuming and costly. In Recent years, computational simulation was introduced in studying photoacoustic signal. However complex equation modelling and numerical analysis are required. Therefore there is a need for an easy and fast simulation technique that helps in understanding the photoacoustic signal generated from various shapes of nanoparticles. k-Wave is a free accessed MATLAB based simulation toolbox which provide the ability to simulate photoacoustic signal in time domain given the initial pressure distribution of the target object. In this work, k-Wave simulation toolbox was used to simulate the photoacoustic signal generated from various shapes of nanoparticles. Seven shapes of nanoparticles are created mainly sphere, cylinder, hollow cylinder, cube, hollow cube, triangle, and nano star. A point sensor (ultrasound detector) is used to detect the photoacoustic signal generated by different shapes of nanoparticles. The simulated photoacoustic signal is presented in the form of frequency response and photoacoustic pressure graph which will be then used in understanding the impact of the shapes on photoacoustic signal characteristics.